2019
DOI: 10.1074/jbc.ac118.006041
|View full text |Cite
|
Sign up to set email alerts
|

A novel thyroid hormone receptor isoform, TRβ2-46, promotes SKP2 expression and retinoblastoma cell proliferation

Abstract: Edited by Xiao-Fan Wang Retinoblastoma is a childhood retinal tumor that develops from cone photoreceptor precursors in response to inactivating RB1 mutations and loss of functional RB protein. The cone precursor's response to RB loss involves cell type-specific signaling circuitry that helps to drive tumorigenesis. One component of the cone precursor circuitry, the thyroid hormone receptor ␤2 (TR␤2), enables the aberrant proliferation of diverse RB-deficient cells in part by opposing the down-regulation of S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Changes in the transcriptional activity of the SKP2 gene were analyzed most often in the context of carcinogenesis. It is indicated that this gene may become a new molecular marker of the carcinogenesis process, because its overexpression is associated with a worse prognosis [ 78 – 80 ]. Also in relation to PRKAR2B , we found that CsA reduced the level of its expression, which is consistent with the observations of Zgheib et al [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the transcriptional activity of the SKP2 gene were analyzed most often in the context of carcinogenesis. It is indicated that this gene may become a new molecular marker of the carcinogenesis process, because its overexpression is associated with a worse prognosis [ 78 – 80 ]. Also in relation to PRKAR2B , we found that CsA reduced the level of its expression, which is consistent with the observations of Zgheib et al [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRβ1 suppresses SKP2 to prevent S-phase entry and progression and thus acts as a safeguard against tumorigenesis associated with RB1 loss [ 71 ]. In contrast, a new oncogenic isoform of TRβ2, TRβ2-46, increases expression and stability of the SKP2 protein, which counteracts the TRβ1 tumor-suppressive function and thus promotes the proliferation of retinoblastoma cells [ 68 ] ( Figure 1 C). Counteraction between TRβ1 and TRβ2 also confers minimal genomic instability, which may be responsible for decreased aneuploidy, so that tumors escape from possible death due to chromosomal abnormalities in rapidly proliferating retinoblastoma cells [ 25 ].…”
Section: Molecular and Cellular Basis Of Retinoblastomamentioning
confidence: 99%
“…However, some other premalignant cells (weak orange) undergo cell cycle arrest and senesce, becoming retinoma that often develop into retinoblastoma [ 3 , 17 ]. ( C ) Cone-associated proteins are present in tumor cells [ 46 , 48 ], while cone circuitry facilitates development of retinoblastoma [ 17 , 25 , 26 , 46 , 67 , 68 , 69 , 70 , 71 ]. A cone-specific signal circuitry is linked with the pRB pathway through S-phase kinase associated protein 2 (SKP2), whose activity is suppressed through an N-terminal interaction with pRb [ 72 ].…”
Section: Figurementioning
confidence: 99%
“…The RB1 gene codes for pRB, which is an almost ubiquitously expressed phosphoprotein of 928 amino acids. Loss of functional pRB leads to a response that alters the cell type-specific signaling circuitry, which helps to drive tumorigenesis of retinoblastoma [ 8 , 9 ]. In cells with normal RB1 alleles, dephosphorylated pRB binds E2F-transcription factors and blocks transition from G1- to S-phase.…”
Section: Introductionmentioning
confidence: 99%